2021
DOI: 10.3390/ijms22042129
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinomas with Stromal B7-H3 Expression Have Lower Intratumoural CD8+ T Cell Density

Abstract: CD8+ T cells are the main effector cells of anti-cancer immune response that can be regulated by various costimulatory and coinhibitory molecules, including members of the B7 family. B7 homolog 3 (B7-H3) appears as a promising marker for immunotherapy; however, its significance in gastric cancer (GC) is unclear yet. We evaluated the spatial distribution of CD8+ T cells in relation to the expression of B7-H3 by double immunohistochemical staining. The level of B7-H3 intensity was scored manually (0–3) and dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In contrast, in stomach cancer cell lines and xenograft models, it was revealed that B7-H3 knockdown significantly inhibited cancer invasion and metastasis capacity [ 150 ]. Mechanistically, B7-H3 + neutrophils have been found in gastric cancer tissues, which increases tumor progression and is a negative predictive marker of reduced survival [ 94 ], and a more restricted CD8 + T cell location was noted in B7-H3-high gastric cancer samples, indicating a potential immunosuppressive role of B7-H3 in gastric cancer, although no significant survival difference was observed between the B7-H3-high and B7-H3-low groups in the study [ 151 ]. Evidence for the role of B7-H3 in gastric cancer is limited and conflicting, and more studies, particularly in patients with gastric cancer, are warranted.…”
Section: B7-h3 In Different Malignanciesmentioning
confidence: 99%
“…In contrast, in stomach cancer cell lines and xenograft models, it was revealed that B7-H3 knockdown significantly inhibited cancer invasion and metastasis capacity [ 150 ]. Mechanistically, B7-H3 + neutrophils have been found in gastric cancer tissues, which increases tumor progression and is a negative predictive marker of reduced survival [ 94 ], and a more restricted CD8 + T cell location was noted in B7-H3-high gastric cancer samples, indicating a potential immunosuppressive role of B7-H3 in gastric cancer, although no significant survival difference was observed between the B7-H3-high and B7-H3-low groups in the study [ 151 ]. Evidence for the role of B7-H3 in gastric cancer is limited and conflicting, and more studies, particularly in patients with gastric cancer, are warranted.…”
Section: B7-h3 In Different Malignanciesmentioning
confidence: 99%
“…The decrease in the number and dysfunction of CD8 + T cells is one of the reasons for gastric cancer immune tolerance. In GC tissues with high expression levels of B7-H3 (CD276), the density of CD8 + T cells within the tumor was reduced, suggesting that B7-H3 may be involved in the mechanism of tumor evasion of immune responses ( 17 ). Toll-like receptor 2 (TLR2) was down-regulated in CD8 + T cells of gastric cancer patients, and TLR2 activation could increase the expression of perforin and granzyme B in CD8 + T cells and enhance CD8 + T cells cytotoxicity ( 18 ).…”
Section: The Constitution Of Gc Tmementioning
confidence: 99%
“…By immunohistochemistry and analysis of the digital image, Ulase et al demonstrated that B7-H3 is expressed chiefly in the stromal compartment of patients with GC, and CD8+ T lymphocytes are inhibited in tumors with excessive expression of B7-H3. As a result, they reported that B7-H3, as a considerable target of GC immunotherapy, can regulate cell-mediated immunity responses in patients of Western origin [ 108 ]. Accordingly, the findings of various studies demonstrated that expression of B7-H3 is increased in GC patients.…”
Section: B7-h3 (Cd276)mentioning
confidence: 99%